EFEKTIVITAS ORGANISASI DALAM KAITANNYA DENGAN DAUR HIDUP ORGANISASI - FX Supriyono (Center for Economic Studies Universitas Katolik Parahyangan, 2000)
Measuring organization effectiveness has not so simple matter. It is because organization has no single objectives that must be met in a certain period of time Therefore, you cannot say that a certain organization is an effective organization merely because of its profits or something like that. What you should do is using an appropriate approach to determine its effectiveness, such as the goal-attainment; internal process model; system model or the human relation model.In using a certain approach to evaluate, you must consider what we say an organization life cycle. Why? It is because in each stage of the life cycle contains unique characteristics that are different each other. When the organization is in an entrepreneurial stage, you should not evaluate its effectiveness by using goal attainment model but you have to apply the system model. Also, when a certain organization has reached its growth in its cycle, you must use the human relation model to evaluate. Finally, I would like to say that actually there is no precise operational definition of the organization effectiveness. It is because of its Complexities.